Sanctity of time and space in tradition and modernity - Houtman, Alberdina.; Poorthuis, Marcel, 1955-; Schwartz, Joshua. (Jewish and Christian Perspectives Series;, 1998)
Time and space can take on a sacred nature in both Judaism and Christianity accompanied by a permanent critical attitude towards the sacred. Conceptions of sacredness imply a conception of community and of society at large. This study investigates the different attitudes toward sacred time and space from an interdisciplinary perspective, ranging from the Biblical period through Qumran, Patristics, Rabbinics, archaeology and theology to modern and even to post-modern rituals. This approach offers a fascinating insight into both the common heritage of Judaism and Christianity and their mutual differences.